Prevalence of co-infection of human immunodeficiency virus in diagnosed tuberculosis cases: Meta-analysis - Alanazi, Naif H; Hanif, Asif (International Journal of Health Sciences, 2024)
Objective: The objective of the study was to find pooled prevalence and risk factors of co-infection of human immunodeficiency virus (HIV) in diagnosed tuberculosis (TB) cases. Methods: Search engines including PubMed and Google Scholar were used to find literature using search terms such as “co-infection,” “HIV,” “Acquired Immunodeficiency Syndrome,” TB and “Prevalence” among others. All original studies conducted on the prevalence of HIV co-infection among diagnosed TB patients that were freely available in full length had a clear methodology and relevant results were included in the study. Results: From 1021 initial studies, a total of 18 studies were selected for analysis. A total of 18 studies were included with a total sample size of 44943. The minimum prevalence of HIV-TB was reported in a study from Pakistan as 0.29% and the maximum prevalence of HIV-TB was found in Nigeria, that is, 44.20%. The pooled prevalence of HIV/TB co-infection was 16.291% (95%; 9.57–24.38) using the random effect method. As per Begg’s test, there was no publication bias. As I2 is 99.74% so, there is high heterogeneity among studies; hence, random effect model is preferred. Conclusion: The study concludes that the pooled prevalence of HIV/TB co-infection was found to be 16.291% (95%; 9.57–24.38). The risk of mortality will be substantially raised by the co-existence of HIV-TB co-infection, so early screening and emphasizing the urgent need for integrated health-care interventions can cope with the situation.